PENYEBAB KETIDAKHADIRAN PESERTA DIDIK DALAM PROSES BELAJAR MENGAJAR DI SMP NEGERI 11 PADANG - Fauzia, Mita; Sano, Afrizal; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This study aimed to describe the causes of absenteeism of students in teaching and learning at Junior High School 11 in Padang, the purpose of the study was to describe 1). The cause of absenteeism of students seen from itself (internal) at Junior High School 11 Padang and 2). The cause of absenteeism of students seen from outside (external) at Junior High School 11 in Padang. This research is descriptive. With a population of learners in grade VIII, and IX which totaled 62 people. The techniques used in the collection of data on research in the form of non-test instrument is questionnaire were processed using a percentage formula. Results of research conducted can be described as follows: 1). The cause of absenteeism of students seen from itself (internal) at Junior High School 11 Padang fall into many categories, namely the average percentage of 14,6% and 2). Peyebab absence learners viewed from outside himself (external) at Junior High School 11 Padang fall into many categories, namely the average percentage of 13,2%. Based on the study is expected to teachers or the school, family and more attention to the problem of absenteeism of students to teaching and learning activities can be carried out and organized well and provide guidance and direction to students continuing to always pay attention to the activities of learners in the school.